2013
DOI: 10.1111/pai.12106
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in children with food allergy on specific elimination diets

Abstract: BACKGROUND Children with food allergy have been shown to have increased small intestinal permeability (IP) following ingestion of the offending food as well as during elimination diets. We investigated IP in asymptomatic food-allergic children during an elimination diet to identify clinical characteristics associated with altered IP. METHODS Urinary recovery ratios of lactulose and mannitol (L/M) were determined five hours following ingestion of 7.5 g of lactulose and 2 g of mannitol in 131 cow’s milk- and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…Strikingly, simply increasing small intestinal paracellular permeability induced a systemic and local immune response to OVA. 34 Interestingly, our experiments showed that increasing small intestinal permeability in a healthy host increases antigen-specific IgE in the small intestine, suggesting a possible role of small intestinal permeability in food allergy development. In a host genetically predisposed to inflammation, such as the IL-10 2/2 mouse, or in the presence of a bacterial antigen instead of a dietary one, the immune response in the presence of an increased small intestinal permeability may be one of cell-mediated immunity instead of a humoral response, leading to a chronic inflammatory state and tissue injury.…”
Section: Discussionmentioning
confidence: 68%
“…Strikingly, simply increasing small intestinal paracellular permeability induced a systemic and local immune response to OVA. 34 Interestingly, our experiments showed that increasing small intestinal permeability in a healthy host increases antigen-specific IgE in the small intestine, suggesting a possible role of small intestinal permeability in food allergy development. In a host genetically predisposed to inflammation, such as the IL-10 2/2 mouse, or in the presence of a bacterial antigen instead of a dietary one, the immune response in the presence of an increased small intestinal permeability may be one of cell-mediated immunity instead of a humoral response, leading to a chronic inflammatory state and tissue injury.…”
Section: Discussionmentioning
confidence: 68%
“…Along these lines, increased gut permeability has been found in children with food allergies 50 and it has also been recently detected in asthmatic patients. 51 The homeostasis of the intestinal epithelium is maintained by a complex interplay of multiple regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Lactulose/mannitol ratios (L/M ratio) were considered abnormal when they exceeded 0.03 [22]. Small intestinal bacterial overgrowth was identified using a hydrogen breath test (H2BT) apparatus (Bedfont Scientific Ltd., Maidstone, Kent, UK).…”
Section: Methodsmentioning
confidence: 99%